EKSPLORASI PEMBELAJARAN KOOPERATIF STAD BERBANTUAN MEDIA VIDEO ANIMASI TERHADAP MINAT BELAJAR BIOLOGI: KAJIAN EKSPERIMENTAL - Saleh, Andi Rahmat; Daud, Firdaus; Khoirunnisa, Araminta Diah (Universitas Tanjungpura, 2024)
The purpose of this study was to determine how the STAD type cooperative learning model, in conjunction with animated video content, affected the biology learning interest of SMAN 4 Maros students on plant tissue subject. This study used a quasi-experimental design with two groups: an experimental group and a control group. The pretest-postest control group design was used for the research. The study of this research is XI MIPA 5 as the experimental group and XI MIPA 7 as the control group. A learning interest questionnaire consisting of 20 statements is the research instrument. Statistical inferential and descriptive analysis is the method of data analysis employed. The result of descriptive analysis shows that the final average interest learning score in the experimental group is 84,37 and it is higher than the control group which was 78,97. The result of inferential analysis with the anacova test shows that there was an influence of the STAD Type Cooperative Learning Model with the help of animated video media on Biology Learning Interest of Students at SMAN 4 Maros On Plant Tissue Subject.